Traffic Jams: Analysing Everyday Life through the Immanent Materialism of Deleuze & Guattari - Cole, David R. (David Robert), 1967-; Project Muse; Project Muse. (Project Muse, 2020)
This dead letter presents a rendition and exploration of the immanent materialism of Deleuze & Guattari as theorised in 1000 Plateaus and as a means to analysing everyday life. The evidence that will be presented to back up and expand upon such an analysis consists of art, film and objects from life that relate to and suggest the complex ways in which we are affected by traffic jams. A picture of a reciprocating substrata of everyday life is presented that includes and builds upon the unconscious, and shows how the abstract turbulence of everyday life forms eddies and flows that may be followed and understood. The immanent materialism of Deleuze & Guattari is a philosophical construction that leads to the formation of 'plateaus' as they were executed in A Thousand Plateaus. The plateau of this dead letter is [21 October 2011: the Petro-Citizen]. The writing contained here populates this plateau with traffic jams, car crashes, global environmental concerns and the psychological and sociological contingencies that accompany the petro-citizen. Connections between the strata that make up the plateau of the petro-citizen will deliberately be left as open-ended and speculative to show how the petro-citizen functions as a flagrant construct in everyday life, and such a postulation and designation includes the desire for petrol and explains the resulting panpsychic petro-political landscape. The double-articulation of the plateau will be explored in this letter through the ways in which the petro-citizen and petro-politics create reciprocating realms of motivation and drive that tend towards contemporary double-articulation, paradox and contradiction with respect to the usages of oil. In this letter, the double-articulation results in a multiple chequered flag or illusionary global end game that designates the current human relationships with oil.
The petro-citizen -- Immanent materialisms of everyday life -- Car crashes and the death drive -- Time-images of car crashes and traffic jams -- Libidinal carism -- The plateau of the petro-citizen -- Global car crashes and traffic jams -- China & the North Pacific Gyre -- Epilogue--ode to Michael Douglas.
Issued as part of book collections on Project MUSE.
Includes bibliographical references (pages [41]-43).
Description based on print version record.
Keywords: Guattari, Felix, -- 1930-1992.; Deleuze, Gilles, -- 1925-1995.; Materialism; Automobile travel -- Philosophy; Traffic congestion -- Philosophy; Petroleum industry and trade -- Philosophy; Life; Electronic books; Electronic books